Mesenchymal Stem Cells Ameliorate Atherosclerotic Lesions via Restoring Endothelial Function. (10th December 2014) - Lin, Yu-Ling; Yet, Shaw-Fang; Hsu, Yuan-Tong; Wang, Guei-Jane; Hung, Shih-Chieh
Abstract : The effects of mesenchymal stem cells (MSCs) on endothelial dysfunction and atherosclerosis were investigated in human/mouse endothelial cells treated with oxidized low-density lipoprotein and in apolipoprotein E-deficient (apoE −/− ) mice fed a high-fat diet. MSC transplantation improved endothelial function and plaque formation, and activation of the Akt/endothelial nitric-oxide synthase pathway in endothelium by interleukin-8/MIP-2 is involved in the protective effect of MSCs. The study supports the use and clarifies the mechanism of MSCs for ameliorating atherosclerosis. Abstract: Transplantation of mesenchymal stem cells (MSCs) is beneficial in myocardial infarction and hind limb ischemia, but its ability to ameliorate atherosclerosis remains unknown. Here, the effects of MSCs on inhibiting endothelial dysfunction and atherosclerosis were investigated in human/mouse endothelial cells treated with oxidized low-density lipoprotein (oxLDL) and in apolipoprotein E-deficient (apoE −/− ) mice fed a high-fat diet. Treatment with oxLDL inactivated the Akt/endothelial nitric-oxide synthase (eNOS) pathway, induced eNOS degradation, and inhibited nitric oxide (NO) production in endothelial cells. Coculture with human MSCs reversed the effects of oxLDL on endothelial cells and restored Akt/eNOS activity, eNOS level, and NO production. Reduction of endothelium-dependent relaxation and subsequent plaque formation were developed in apoE −/− mice fed a high-fat diet. Systemic infusion with mouse MSCs ameliorated endothelial dysfunction and plaque formation in high-fat diet-fed apoE −/− mice. Interestingly, treatment with interleukin-8 (IL8)/macrophage inflammatory protein-2 (MIP-2) alone induced the similar effects of human/mouse MSCs on oxLDL-treated human/mouse endothelial cells. Neutralization antibodies (Abs) against IL8/MIP-2 also blocked the effects of human/mouse MSCs on oxLDL-treated human/mouse endothelial cells. Consistently, MIP-2 injection alone induced the similar effect of MSCs on the endothelial function in high-fat diet-fed apoE −/− mice. The improvement in endothelial dysfunction by mouse MSCs was also blocked when pretreating MSCs with anti-MIP-2 Abs. In conclusion, MSC transplantation improved endothelial function and plaque formation in high-fat diet-fed apoE −/− mice. Activation of the Akt/eNOS pathway in endothelium by IL8/MIP-2 is involved in the protective effect of MSCs. The study helps support the use and clarify the mechanism of MSCs for ameliorating atherosclerosis.